Value generation analysis within the design process of construction projects in Chile - Zulay Giménez; Rodrigo F. Herrera; Omar Sánchez (Ain Shams Engineering Journal, 2024)
Value generation occurs during the life cycle of construction projects. However, the ability to influence the projects' characteristics at the design stage increases the probability of maximizing value. Nevertheless, few studies assess value creation during the design. Considering this gap, the aim of this paper is to analyze the value generated at the design stage of Chilean construction projects. The research method responds to a descriptive type of study consisting of three stages: design value attributes definition, assessment and quantitative measurement of value applying a Value Analysis Model recently developed, and value comparison. Twenty-eight value attributes were selected from literature review and grouped into seven satisfaction conditions. The value assessment was performed through a questionnaire applied to 47 Chilean companies within the construction industry. The main findings show that 1) companies, in general, have low-value expectations related to the design process and, in turn, low-value generation, which can be negatives values; 2) projects tend to compensate the lack of indispensable attributes with the inclusion of attractive features, thereby demonstrating an absence of prioritization; and 3) the satisfaction conditions with the highest value generation are business environment, schedule and budget, and with lowest value generated are deliverables, integration and tools and technology. The primary contribution of this study is be useful to designers, managers and researchers, as it provides information on focus attributtes that require appropriate care to improve value within design-build processes; and for any project or company wanting to know its value benchmarking concerning other projects.